NIHAO XIII: clumpy discs or clumpy light in high-redshift galaxies? - Buck, Tobias; Macciò, Andrea V.; Obreja, Aura; Dutton, Aaron A.; Domínguez-Tenreiro, Rosa; Granato, Gian Luigi (Monthly notices of the Royal Astronomical Society, 2017)
Many massive star-forming disc galaxies in the redshift range 3-0.5 are observed to have a clumpy morphology showing giant clumps of size ∼1 kpc and masses of about 107-1010  M⊙. The nature and fate of these giant clumps are still under debate. In this work, we use 19 high-resolution simulations of disc galaxies from the Numerical Investigations of Hundred Astrophysical Objects (NIHAO) sample to study the formation and evolution of clumps in the discs of high-redshift galaxies. We use mock Hubble Space Telescope-CANDELS observations created with the radiative transfer code grasil-3d to carry out, for the first time, a quantitative comparison of the observed fraction of clumpy galaxies and its evolution with redshift with simulations. We find a good agreement between the observed clumpy fraction and the one of the NIHAO galaxies. We find that dust attenuation can suppress intrinsically bright clumps and enhance less luminous ones. In our galaxy sample, we find clumps only in light (U band) from young stars but not in stellar mass surface density maps. This means that the NIHAO sample does not show clumpy stellar discs but rather a clumpy light distribution originating from clumpy star formation events. The clumps found in the NIHAO sample match observed age/colour gradients as a function of distance from the galaxy centre, but they show no sign of inward migration. Clumps in our simulations disperse on time-scales of about a hundred Myr and their contribution to bulge growth is negligible.